Theories of InformationTechnological Competence Development in Future Teachers - Begmatova Sevara Nematovna (Genius Journals, 2023)
This article describes the importance of information technology competence in today's modern education and theories about information technology competences.
Keywords: competence; communicative information-competency; information technology competence; criteria